Editorial - Oniwide, Oyetola Olaoluwa (NIU Journal of Humanities, 2018)
This issue of KIU Journal of Humanities touches on development administration, political education, communication and media studies, business and entrepreneurship studies, gender studies as well as legal studies. The first part of the Journal addresses issues in Development Administration such as Aternative Revenue Generation, Women Participation in Community Development, Rural Development, and the Role of the Universal Basic Education Programme in Sustainable Development in Nigeria. It is argued in one of the papers that top bottom approach, political deprivation, lack of enlightenment and awareness campaign and lack of proper educational empowerment constitute the major challenges of community participation in rural development. It is therefore recommended that, the local government should improve in the enlightenment and awareness campaign which can serve as a way of motivating communities to participate in rural development. In part two, the importance of political education in democratic governance of a country is emphasized. Findings of some of the studies show that people watch television programmes occasionally and the programmes influence their voting opinion. Thus, it is suggested that television stations in most African countries should produce more political programmes to increase political awareness and also broadcast these programme on the internet for wider outreach. This corroborates the fact that in today's world, media becomes as essential as our daily needs. Media of today is playing an outstanding role in creating and shaping of public opinion and strengthening of society. Media is the sword arm of democracy. It is against this backdrop that the papers in Part three emphasize the role of Mass Communication in the society. Based on its findings and others not mentioned here, one of the papers in the section argues that, since positive attitude toward sanitation practices depended on regular radio enlightenment campaigns, frequent campaigns by the media are highly needed. It must also be mentioned that in the search for an economic development agenda/program that empowers people, entrepreneurial education is very important in order to achieve a sustainable development. Against this backdrop, the papers in part four amplify that central tenet. Theoretical, methodological and practical implications are discussed in the papers. In particular, the results recommended that entrepreneurship skills acquired through the mandatory entrepreneurship education programme for undergraduate students of tertiary institutions in Nigeria are an important consideration in helping self-employed graduates to enhance their career performance. In the Section on Gender Studies, it is recommended that civil society, NGOs and CBOs should advocate for the need to create income generating activities for women in the sub-country. This is because the involvement of civil society, public consultation, and polling can have different outcomes on income generating activities which can help to promote socio-economic status of the women .     It has been observed that the administration of justice, in all countries and at all times is a subject broad and difficult, both in its operation and its influence. It is perhaps more indicative, a truer test, of the real temper and spirit, both of the government and the people of the state or country, than any other thing. This is why the papers in the last part of this edition focus on Legal Education. On the whole, this edition of KIU Journal of Humanities features many thought provoking articles. Some of these articles are empirical in nature while others have theoretical base. Each of them focuses on one specific social and management problem or the other; trying to proffer solutions to them. Readers are therefore advised to make proper use of the ideas presented by the various authors.